Shorter duration time trial performance and recovery is not improved by inclusion of protein in a multiple carbohydrate supplement - Wolfe, A. S.; Brandt, S. A.; Krause, I. A.; Mavison, R. W.; Aponte, J. A.; Ferguson-Stegall, L. M. (The Journal of Strength and Conditioning Research, 2017)
Ingesting multiple carbohydrate (CHO) types during exercise can improve endurance performance compared with single CHO only. Adding protein to a multiple CHO beverage has been shown to increase cycling time to exhaustion (TTE) compared with a single CHO beverage. However, it is unclear if improvements were due to multiple CHO or protein, and TTE protocols are not representative of typical race events. This study investigated whether adding protein to a multiple CHO beverage improved performance and recovery in 2 same-day cycling time trials (TTs) compared with isocaloric multiple CHO only. Ten cyclists (37.4 ± 8.9 years; VO2max 54.6 ± 6.5 ml/kg/min) performed a familiarization and 2 randomized, crossover, double-blinded experimental trials consisting of pretrial leg strength testing, 40-km TT, 30-min recovery, 10-km TT, and posttrial leg strength testing. Seven 275 ml doses of multiple CHO (MCO) or multiple CHO+protein (MCP) were ingested during the protocol. Blood glucose, lactate, heart rate (HR), and rating of perceived exertion (RPE) were also measured. Continuous variables were analyzed with paired t-tests, and repeated measures with repeated-measures analysis of variance. No differences existed between MCO and MCP in 40-km TT time (81.6 ± 2.8 vs. 81.9 ± 2.9 minutes, respectively, p = 0.94), or in 10-km time (24.0 ± 0.9 vs. 23.9 ± 1.0 minutes, p = 0.97). Blood glucose was higher before 10-km TT in MCO compared with MCP (3.78 ± 0.20 vs. 3.31 ± 0.19 mmol/L, p = 0.002). No treatment differences were found for lactate, HR, RPE, or strength recovery. When using a protocol and performance measures that replicate realistic, shorter duration events, adding protein to a multiple CHO beverage does not improve performance compared with multiple CHO only.